2016
DOI: 10.1007/s10067-016-3453-0
|View full text |Cite
|
Sign up to set email alerts
|

Myositis-specific autoantibodies and their association with malignancy in Italian patients with polymyositis and dermatomyositis

Abstract: This study aims to characterize myositis-specific antibodies in a well-defined cohort of patients with idiopathic inflammatory myopathy and to determine their association with cancer. Sera from 40 patients with polymyositis, dermatomyositis, and controls were tested by protein and RNA immunoprecipitation to detect autoantibodies, and immunoprecipitation-Western blot was used for anti-MJ/NXP-2, anti-MDA5, and anti-TIF1γ/α identification. Medical records were re-evaluated with specific focus on cancer. Anti-MJ/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 23 publications
2
47
3
Order By: Relevance
“…In contrast, heliotrope rash, lateral hip erythema, flagellate erythema, Gottron's sign and/or papules, psoriasis‐like lesions and oral manifestations did not appear to be significantly associated with anti‐TIF‐1γ antibodies. Our study revealed a trend towards an association between anti‐TIF‐1γ antibodies and cancer, unlike most previous studies that established a significant association . The lower frequency of anti‐TIF‐1γ antibodies in our cohort could be an explanation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, heliotrope rash, lateral hip erythema, flagellate erythema, Gottron's sign and/or papules, psoriasis‐like lesions and oral manifestations did not appear to be significantly associated with anti‐TIF‐1γ antibodies. Our study revealed a trend towards an association between anti‐TIF‐1γ antibodies and cancer, unlike most previous studies that established a significant association . The lower frequency of anti‐TIF‐1γ antibodies in our cohort could be an explanation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study revealed a trend towards an association between anti-TIF-1c antibodies and cancer, unlike most previous studies that established a significant association. 9,17,25,29,32,49,50,58,[60][61][62] The lower frequency of anti-TIF-1c antibodies in our cohort could be an explanation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…[15] Rheumatologists also have an interest in CHD4 because it is one of the target antigens for autoantibodies (anti-Mi2) in about 20 per cent of cases of dermatomyositis. [16] However, the relevance of these antibodies to the inflammatory processes of myositis or the malignancies commonly associated with dermatomyositis is unclear.…”
Section: Discussion (643)mentioning
confidence: 99%
“…In general terms, rare autoantibodies in myositis are used to predict more severe forms, including those associated with cancer as many studies support the possibility that DM and PM are paraneoplastic, particularly DM [65]. Some autoantibodies are associated with major recurrence of neoplasms, and these are anti-TIF1γ/α (anti-155-140) and anti NXP2 antibodies [66, 67]. Jo-1 and other anti-aminoacyl tRNA synthetases (anti-ARS) antibodies (PL-7, PL-12, EJ, OJ, KS) are associated with the so-called anti-synthetase syndrome, characterized by myositis, interstitial lung disease, arthritis, mechanic’s hands and Raynaud’s phenomenon [68, 69].…”
Section: The Abc Of Serum Autoantibodiesmentioning
confidence: 99%